Hubungan Stabilitas Kadar Gula Darah Dengan Penurunan Ketajaman Penglihatan Pada Diabetes Melitus Tipe II Didesa Sokaan Kecamatan Krejengan Kabupaten Probolinggo - Cici Lahayati; Dodik Hartono; Achmad Kusyairi (Pusat riset dan Inovasi Nasional, 2023)
Diabetes Mellitus (DM) is a metabolic disease with hyperglycemia characteristics that occurs because abnormality of insulin secretion . Diabetes mellitus can cause eye damage . Study this aim to know the correlation of stability of blood sugar levels with decreased visual acuity in type II diabetes mellitus.This study use analytical study design correlation with approach cross sectional. The technique used purposive with 52 respondents who meet the criteria. The analysis of the data used test Chi-Square. The results of study showed that for stability rate sugar blood of 29 respondents are unstable. Decrease in visual acuity of 23 respondents were in moderate category. The results of the chi-square test of the stability of blood sugar levels with decreased visual acuity in Diabetes Mellitus type II obtained p value = 0.00 0 so that the p -value < = 0.05 . The results of this study indicate a relationship between the stability of blood sugar levels with decreased visual acuity.It can be concluded that unstable blood sugar levels can affect the decrease in visual acuity in Diabetes Mellitus. On the contrary, if blood sugar levels are in a stable range, the risk of decreased visual acuity will decrease.